If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2b + 5) + -18 = -3b + 2 Reorder the terms: 4(5 + 2b) + -18 = -3b + 2 (5 * 4 + 2b * 4) + -18 = -3b + 2 (20 + 8b) + -18 = -3b + 2 Reorder the terms: 20 + -18 + 8b = -3b + 2 Combine like terms: 20 + -18 = 2 2 + 8b = -3b + 2 Reorder the terms: 2 + 8b = 2 + -3b Add '-2' to each side of the equation. 2 + -2 + 8b = 2 + -2 + -3b Combine like terms: 2 + -2 = 0 0 + 8b = 2 + -2 + -3b 8b = 2 + -2 + -3b Combine like terms: 2 + -2 = 0 8b = 0 + -3b 8b = -3b Solving 8b = -3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3b' to each side of the equation. 8b + 3b = -3b + 3b Combine like terms: 8b + 3b = 11b 11b = -3b + 3b Combine like terms: -3b + 3b = 0 11b = 0 Divide each side by '11'. b = 0 Simplifying b = 0
| x+7=2x+7 | | 7x+6(2-x)+11=22+3(6+x) | | z=ry | | 12(-32)= | | 2n+n=9 | | 5+3a=-4 | | x+5y-z=20 | | (3a+14)+(5a-1)=(4a-8) | | 8-x-2y-8x-2y= | | -7x-(10-x)=58 | | x-0.6=9.3 | | X+5y=18 | | 2m^2-16m+34=0 | | 2m^2-16+34=0 | | 4(3y-1)+13=.25(24y-36) | | 2x+3=2(x+4)-5 | | 10x=(1.2)(28) | | (5a-1)+(4a-8)=(3a+14) | | (12x-9)=(10x+15) | | 2v^2-6v+56=v^2-49 | | 4a-6-2a+2= | | -3(5x-2)+x=6(3x+2)+6 | | 7-(7)= | | 5m^2+7m+12=0 | | 4y-2=3x | | 6y-1=-y+20 | | n+9=16*2 | | 49y^3-7y^2+14y=0 | | n+9/2=16 | | 9(t-5)+3t=4(3t+3)-10 | | 2z+3+9z-8= | | n+9*2=16 |